STAKEHOLDER PRESSURE MODERATES THE RELATIONSHIP BETWEEN GREEN INVESTMENT AND ENVIRONMENTAL MANAGEMENT SYSTEMS TO CARBON EMISSIONS DISCLOSURE - Muhamad Abdul Malik; Nofryanti; Holiawati (ZILLZELL MEDIA PRIMA, 2025)
This study aims to examine the moderating effect of stakeholder pressure on the relationship between green investment and environmental management systems on carbon emission disclosure. The research focuses on companies listed in the KOMPAS100 index on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. A quantitative associative approach was employed, with sample selection conducted through purposive sampling and data analyzed using panel data regression models. The findings indicate that green investment does not significantly influence carbon emission disclosure, whereas the implementation of environmental management systems positively affects disclosure practices. Moreover, stakeholder pressure does not moderate the relationship between green investment and carbon emission disclosure. Interestingly, it weakens the positive relationship between environmental management systems and carbon emission disclosure. These results suggest the need for stronger regulatory frameworks and internal mechanisms to encourage transparent and consistent environmental reporting. Enhancing carbon disclosure is a crucial step in supporting Indonesia’s commitment to achieving Net Zero Emissions by 2060.